How far is mitigation of Russian gas dependency possible through energy efficiency and renewable policies assuming different gas market structures?. Issue 1 (March 2017) - Selei, Adrienn; Tóth, Borbála; Resch, Gustav; Szabó, László; Liebmann, Lukas; Kaderják, Péter
This paper presents the results of a coordinated modelling assessment that incorporates European energy efficiency and renewable policies with two potential gas market scenarios. First, the impact of EU energy efficiency and renewable policies on natural gas demand is calculated using the PRIMES model 2014 Baseline projection, the Fraunhofer ISI Low Policy Intensity Energy Efficiency scenario, and the Green-X model for renewable deployment. Next, the effect of these policies on the natural gas markets is assessed, using the European Gas Market Model. The model tests scenarios for different positions on long-term gas contracts with Russia assuming different stages of European gas infrastructure development. The findings show that dependency on Russian natural gas can be reduced to low levels without triggering a significant increase in natural gas prices for any single EU member country. In an extreme scenario whereby energy efficiency savings, higher renewable energy sources deployment and the assumed positive gas market developments take place simultaneously, gas cost savings can reach as high as 37%. Benefits arise not only in the most recent round of EU Member States (12 MS) targeted in the study, but are visible across most EU gas markets. This underlines the interlinkages of the whole EU gas market, and the results suggest that security of gas supply is not only a challenge for new Member States, but in the broader European markets.